2021
DOI: 10.1108/qrj-04-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

A trio of teacher education voices: developing professional relationships through co-caring and belonging during the pandemic

Abstract: PurposeThis research is situated at a metropolitan university in Melbourne (Australia) where the authors work in initial teacher education programs within the same faculty. The purpose of this study is to raise awareness that collegial, collaborative and “co-caring” environments can foster an improved sense of belonging, acceptance and inclusion in the academy. They also argue that communities of practice may foster an improved sense of belonging that enhances empowerment and harmony among all staff in academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Joseph et al. (2022) stress ‘co-caring’ as being vital to academic existence as relationality is deeply embedded in the daily ‘doing’ of academic work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joseph et al. (2022) stress ‘co-caring’ as being vital to academic existence as relationality is deeply embedded in the daily ‘doing’ of academic work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Reshmi's current doctoral research focusing on inclusion on ethnic migrant women in academia draws on the conundrum of colour to describe the headwinds battering this particular minoritised group. This paper contributes to extant literature that places scholars of diverging power positions in conversation with one another (Musselin, 2013; Joseph et al. , 2022) to inform higher education how systemic barriers to inclusion are further exacerbated within the context of the institutional response to the COVID-19 crisis.…”
Section: The Life and Times Of Minoritised Academicsmentioning
confidence: 97%
“…The president of the Australian Association of University Professors (Graeber, 2021) suggested academic work becomes counter-productive when purely inwards facing. For example, Joseph et al (2022) utilised a case study drawing on CAE and showed that collegial (co-caring) environments foster an improved sense of belonging. In WGs scholarly conversations and reflection contribute to collegiality and deepen relationships between participants where a focal topic provides the opportunity to exchange ideas, experiences and reveal vulnerabilities to forge social bonds.…”
Section: Ethics Of Care and Well-beingmentioning
confidence: 99%
“…The president of the Australian Association of University Professors (Graeber, 2021) suggested academic work becomes counter-productive when purely inwards facing. For example, Joseph et al. (2022) utilised a case study drawing on CAE and showed that collegial (co-caring) environments foster an improved sense of belonging.…”
Section: Introductionmentioning
confidence: 99%
“…It combines more experienced members with less experienced members and takes the form of regular meetings to discuss challenges and opportunities (Bean & Hyers, 2014;Donelly & Mcsweeney, 2010). The online variant is hardly new, although it has grown significantly during the pandemic (Joseph, Lahiri-Roy & Bunn, 2022). It offers advantages in terms of reach and scalability to participants, although there are potential weaknesses, too.…”
mentioning
confidence: 99%